Arc Length Inequality for a Certain Class of Analytic Functions Related to Conic Regions. (27th August 2013) - Ul-Haq, Wasim; Arif, Muhammad; Khan, Asfandyar
Abstract : In our present investigation, we introduce a subclass of analytic function associated with conic regions which is a form of generalized close-to-convexity. The arc-length inequality for a class of analytic function is well known. We derive this inequality for the newly defined class and also study some of its interesting consequences.